THE ANALYSIS OF TOP TRENDS OF DEVELOPMENT OF MECHANICAL ENGINEERING IN THE WORLD AND IN KAZAKHSTAN - A. S. Tulemetova; N. N. Zhanakova (Экономика: стратегия и практика, 2019)
The purpose of the study. The engineering industry of Kazakhstan is very complex and according to the SPIID Program [1] includes sectors such as automotive, oil and gas engineering, agricultural engineering, mining engineering, electrical engineering, within which state support is provided to these industries. Despite some positive dynamics in the development of the domestic engineering industry, unfortunately, there are still many problematic sides. The engineering industry is one of those industries that are experiencing a shortage of qualified personnel, the cause of which is the inconsistency of the curriculum with the production requirements, low status of specialties, low wages. If we talk about the automotive industry, and specifically about its production, then, unfortunately, today there is only a small node assembly of cars. To this end, based on a study of the global engineering market using the examples of countries such as the USA, the EU, and China, it seems appropriate to analyze the development of the engineering industry in Kazakhstan and develop recommendations for improving the competitiveness of the domestic engineering market. Research methods. The study used methods of observation, comparison, measurement, analysis, and deduction. Results and conclusions of the study. The main reasons for the non-profitability of domestic engineering products in comparison with foreign counterparts are its higher cost and low quality associated with the use of outdated production technologies in most enterprises of the republic, an excessively high share of imported components, materials, energy, etc. In addition, most of the products of domestic factories are outdated morally and are far inferior to their foreign counterparts in terms of technical and operational indicators.